Exile and the Jews : Literature, History, and Identity - Saperstein, Marc; Berg, Nancy E. (University of Nebraska Press, 2024)
"This first comprehensive anthology examining Jewish responses to exile from the biblical period to our modern day gathers texts from all genres of Jewish literary creativity to explore how the realities and interpretations of exile have shaped Judaism, Jewish politics, and individual Jewish identity for millennia. Ordered along multiple arcs-from universal to particular, collective to individual, and mythic-symbolic to prosaic everyday living-the chapters present different facets of exile: as human condition, in history and life, in holiday rituals, in language, as penance and atonement, as internalized experience, in relation to the Divine Presence, and more. By illuminating the multidimensional nature of "exile"-political, philosophical, religious, psychological, and mythological-widely divergent evaluations of Jewish life in the Diaspora emerge. The word "exile" and its Hebrew equivalent, galut, evoke darkness, bleakness-and yet the condition offers spiritual renewal and engenders great expressions of Jewish cultural creativity: the Babylonian Talmud, medieval Jewish philosophy, Golden Age poetry, and modern Jewish literature. Exile and the Jews will engage students, academics, and general readers in contemplating immigration, displacement, evolving identity, and more. "-- Provided by publisher.
Keywords: Jewish literature.; Exiles' writings.; Exile (Punishment) in literature.; Jewish diaspora in literature.; Littérature juive.; Littérature de l'exil.; Bannissement dans la littérature.; Diaspora juive dans la littérature.; Judaica.; SOCIAL SCIENCE / Emigration & Immigration.; HISTORY / Jewish.